2013
DOI: 10.2337/dc12-1428
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Performances Over 9 Years of a Selective Screening Strategy for Gestational Diabetes Mellitus in a Cohort of 18,775 Subjects

Abstract: OBJECTIVEWe aimed to evaluate a selective screening strategy for gestational diabetes mellitus (GDM) based on the presence of risk factors: BMI ≥25 kg/m2, age ≥35 years, family history of diabetes, personal history of GDM, or birth of a child with macrosomia.RESEARCH DESIGN AND METHODSOf 20,630 deliveries between 2002 and 2010, we selected 18,775 deliveries in women with no known diabetes and for whom all risk factors were known. GDM was universally screened and defined as fasting plasma glucose level ≥5.3 mmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
4
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 26 publications
9
70
4
7
Order By: Relevance
“…The rate of adverse events in this group was similar to all the other women with GDM. Similar findings have been recently reported (24,25).…”
Section: Discussionsupporting
confidence: 80%
“…The rate of adverse events in this group was similar to all the other women with GDM. Similar findings have been recently reported (24,25).…”
Section: Discussionsupporting
confidence: 80%
“…However, the rate of GDM was particularly high, more than 13% in all of the groups, as we already observed in our total cohort [33], and the possibly greater risk associated with PCOS/ovarian induction or stimulation/ART might have been concealed by the high rate of GDM and its risk factors in our specific population [33], some of which are also possible risk factors for infertility (age, obesity).…”
Section: Discussionsupporting
confidence: 72%
“…It was observed that the presence of conventional risk factors as reported in the French guidelines was indeed predictive of GDM and associated with a poorer prognosis, independently of GDM status [17]. However, this selective screening would have missed one-third of the women with GDM who, even without risk factors, still had more events than women without GDM.…”
Section: Proposalmentioning
confidence: 96%